Continuous‐Time Methods in Finance: A Review and an Assessment - Sundaresan, Suresh M. (Journal of Finance, 2000)
I survey and assess the development of continuous‐time methods in finance during the last 30 years. The subperiod 1969 to 1980 saw a dizzying pace of development with seminal ideas in derivatives securities pricing, term structure theory, asset pricing, and optimal consumption and portfolio choices. During the period 1981 to 1999 the theory has been extended and modified to better explain empirical regularities in various subfields of finance. This latter subperiod has seen significant progress in econometric theory, computational and estimation methods to test and implement continuous‐time models. Capital market frictions and bargaining issues are being increasingly incorporated in continuous‐time theory.